2020
DOI: 10.1088/1757-899x/850/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cuckoo search algorithm for support vector machine parameters optimization in pre collision warning

Abstract: Nowadays, pre-collision warning is one of the substantial aspects of the transportation sector. One of the steps to detect the collisions is by classifying and predicting the collisions. There are many supervised machine learning algorithms used, such as Least Square – Support Vector Machine (LS-SVM). Radial Based Function (RBF) is one of the LS-SVM kernels, which is a well-known method to support reliable performance. However, C and Gamma of its parameters are chosen randomly. This makes the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Mapping low-dimensional nonlinear data to high-dimensional spatial data by nonlinear transformation, the nonlinear support vector machine achieved great performance in the majority of the previous studies. To date, an increasing number of SVMs are optimized by nature-inspired metaheuristic methods to solve classification and prediction problems in engineering [32]. Yusen Liu et al proposed the GWO-SVM to predict the hitch of internal resistance and contact resistance of lead-acid batteries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mapping low-dimensional nonlinear data to high-dimensional spatial data by nonlinear transformation, the nonlinear support vector machine achieved great performance in the majority of the previous studies. To date, an increasing number of SVMs are optimized by nature-inspired metaheuristic methods to solve classification and prediction problems in engineering [32]. Yusen Liu et al proposed the GWO-SVM to predict the hitch of internal resistance and contact resistance of lead-acid batteries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, it has a strong robustness and high search efficiency. However, in the process of optimization, it has been found that Cuckoo search algorithm emerges with some drawbacks such as slow convergence speed and long operation time [30]. In order to overcome the shortcomings of CS and improve the accuracy and efficiency of optimization, the concept of random weight is introduced to improve CS.…”
Section: Modification Of Cuckoo Search Algorithmmentioning
confidence: 99%